Microcystins: Potent xenobiotics - Ilić Maja (Archive of Oncology, 2011)
Having in mind that exposure to low levels of microcystin in drinking water represents the health risk for people, microcystins can be observed as potent xenobiotics. The consequences of exposure to natural products of the blue-green algae, the microcystins, are numerous. Among other things, there is a possibility of development of malignant disease of colon and liver. The occurrence of the tumor is, on one side, enabled by the active transportation of microcystin for achievement of high concentration intracellularly and, on the other side, by high affinity of microcystins for serine/threonine phosphatase PP1 and PP2A after which follows their inactivation. The system, which is responsible for the active transportation of microcystin, is a family of polypeptides for transportation of organic anions (OATP). Isoforms of these carriers are distributed in one tissue, like OATP1B1 and OATP1B3, which are specific for liver or many tissues, OATP1A2 carrier, present in the liver, kidney, brain and the small intestine. The consequences of high concentration of microcystin intracellularly, binding and the inhibitions of protein phosphatase, are numerous. For the occurrence of a tumor, the changes in the nucleus are important, which are related to the gene expression changes, changes in the system for damaged DNA repair and the changes in mitosis. Mediators of these changes have their role in protein activity regulation, signal transmission in the cell, damaged DNA repair, performance of the cell cycle, apoptosis, tumor suppression, cell proliferation and differentiation. Phosphatase inhibition is observed as the strategy of development of a new group of anticancer agents. As phosphatase inhibitors, microcystins and analogs are applied, possibly having the potential to express the difference in toxicity mechanism and detoxification mechanism between the healthy and the tumor cell of liver. High expression of OATP1B1 and OATP1B3 microcystin transporters in hepatocellular carcinoma would confirm selective impact of phosphatase inhibitors to the tumor cell.